The Principal Strategy for Improving the Quality of Learning at an Integrated Islamic Elementary School - Noviyana Rustam; Murniati Murniati; Niswanto Niswanto (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to gather information about the principal's strategy and program for enhancing the quality of learning at SD IT Nurul Ishlah Banda Aceh. The researchers employed a descriptive method in conjunction with a qualitative analysis approach to address the study's difficulties and objectives. It relates to the consideration of data described in the context of the research site's reality. Interview guidelines and observation sheets were utilized as instruments. The Miles and Huberman model was used to analyze the data. The findings indicate that the principal's strategy for improving the quality of learning is based on planning, specifically on developing school programmes that adhere to eight educational standards and three quality standards established by the Integrated Islamic School Network (JSIT). It also needs to build the capacity of teachers and staff to improve the quality of learning, conduct coaching and self-development activities for students, and create an atmosphere of learning based on Ukhuwah Islamiah/family ties in Islam.